Uncatalysed Polycondensation of Lactic Acid to Polylactic Acid under Microwave Irradiation: Effect of Microwave Power - Shikh Mohd Shahrul Nizan Shikh Zahari; Dzulfadli Rosli; Shahrul.zahari; Mansor M.H.; Azman H.H. (Institute of Physics Publishing, 2024)
Indexed by Scopus/ERA